Pendampingan Pengisian Kuisioner Online Berbasis Qtafi Bagi Alumni STKIP Andi Matappa - Muhammad Taqwa; Firdha Razak (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
In obtaining information or feedback from alumni, universities require methods to be used in this regard, one of which is tracer study. Through tracer study, universities will know the educational outcomes of alumni in the form of transition from the world of higher education to the world of work and improvement and quality development of the college education system that they obtained during the lecture. STKIP Andi Matappa is a private university that routinely conducts tracer studies every year. However, many alumni of STKIP Andi Matappa still do not understand and are aware of the importance of tracer study. This is exacerbated by the many alumni of STKIP Andi Matappa who live in remote areas. STKIP Andi Matappa conducted qtafi online questionnaire filling assistance for tracer study with simulation training method at STKIP Andi Matappa alumni in 2019. The purpose of the mentoring activity is increased knowledge and understanding of alumni regarding the filling of QTAFI online questionnaires. The steps of QTAFI-based tracer study questionnaire filling assistance activities for STKIP Andi Matappa alumni are (1) Introduction stage, (2) Explanation of fill data in QTAFI-based tracer study questionnaire, (3) Technical guidance on filling out QTAFI-based tracer study questionnaires. The results of the dedication showed the increasing knowledge and understanding of Graduate of STKIP Andi Matappa regarding the filling of QTAFI online questionnaires for tracer study.